Studies on Influence of Rotary Blade and Peg Type Puddlers on Soil Physical and Dynamic Properties and Rice Yield - Chaudhary, V P; Varshney, B P (Journal of Agricultural Engineering, 2008)
The experiments were conducted to evaluate the influence of rotary blade and peg type puddlers on soil physical and dynamics properties and their subsequent effect on rice yield. Results revealed that the puddling index and hydraulic conductivity were better, in rotary blade as compared to peg type puddled field. The puddling index increased with increasing level of puddling. The bulk density of puddled field increased with the level of puddling as well as time after puddling in all the treatments. Hydraulic conductivity decreased after puddling. Cone index (0-15 cm depth) was found to decrease after puddling over that of initial saturated soil and the reduction was observed more in case of rotary blade as compared to peg type puddled field. Since, there was no significant difference in grain yield with reduced level of puddling, rotary and peg type puddler may be used with one pass so as to minimize the sedimentation period for transplanting operation.